Peran Kebijakan Dividen dalam Memediasi Pengaruh Keputusan Investasi dan Profitabilitas Terhadap Nilai Perusahaan - Anita, Sri; Zakiyah, Tuti (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2023)
This research aims to determine the effect of investment decisions proxied by PER, profitability proxied by NPM, dividend policy proxied by DPR on company value proxied by PBV in Consumer Goods Industrial Sector Companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. . The analysis technique used in this research is path analysis. The research results show that investment decisions (PER) have no significant effect on dividend policy (DPR), profitability (NPM) have a significant effect on dividend policy (DPR), investment decisions (PER) have a significant effect on firm value (PBV), profitability (NPM) significant effect on company value (NPM), dividend policy (DPR) has a significant effect on company value (PBV), investment decisions (PER) on company value (PBV) through dividend policy (DPR) shows that investment decisions have no effect on company value through dividend policy, profitability (NPM) on company value (PBV) through dividend policy (DPR) shows that profitability has no effect on company value through dividend policy